The Role of Perioperative Chemotherapy in the Management of Colloid Carcinoma of the Pancreas. Issue 3 (March 2021) - Picado, Omar; Dosch, Austin R.; Garcia-Buitrago, Monica T.; Yakoub, Danny; Dudeja, Vikas; Rodgers, Steven E.
Abstract : Objectives: Colloid carcinoma (CC) of the pancreas is associated with an improved prognosis compared with pancreatic ductal adenocarcinoma (PDAC), yet studies on the optimal management of these rare lesions are lacking. Methods: Patients with CC or PDAC treated from 2004 to 2014 were identified in the National Cancer Database. Clinicopathologic characteristics were compared between groups and stratified by disease stage. Survival analysis evaluating the role of perioperative chemotherapy was performed. Results: A total of 1295 CC patients (11%) and 10, 855 PDAC patients (89%) were identified. Pancreatic ductal adenocarcinoma was associated with a higher likelihood of mortality compared with CC (hazard ratio, 1.35; 95% confidence interval, 1.25–1.45; P < 0.001). When stratifying by stage, perioperative chemoradiation improved overall survival in early stage (I/IIA) PDAC but had no effect in CC patients. However, for node-positive disease (stage IIB), median overall survival was improved with adjuvant chemoradiation for both CC patients (22 vs 13 months; P < 0.001) and PDAC patients (20 vs 11 months; P < 0.001) compared with surgery alone. Conclusions: Surgery alone may be sufficient for the management of node-negative (I/IIA) CC lesions in contrast to conventional PDAC, whereas CC patients with stage IIB disease have a survival benefit from perioperative chemoradiation. Abstract : Supplemental digital content is available in the text.